Potential applications for climate services originated from the CLIMAX project - Cavalcanti, Iracema F. A.; Coelho, Caio A. S.; Rezende, Luiz Felipe; Gomes, Jorge L.; von Randow, Celso (Frontiers in Climate, 2022)
CLIMAX (Climate Services Through Knowledge Co-Production: A Euro-South American Initiative For Strengthening Societal Adaptation Response to Extreme Events) was an international project funded by FAPESP-Belmont forum developed during the 2016-2021 period. Germany, France, Netherlands, Argentina/France and Brazil were the international partners who worked in common objectives and tasks. The project was composed of four main Work Packages (WP), which interacted to achieve the final goal of developing potential applications to climate services. Here, some of the research and results conducted by the team in Brazil, aiming at the application by climate services in several sectors, mainly in the energy sector are presented, some including international partner collaborations. The WP0- Co-design and Co-Production of Knowledge, was developed in collaboration with the energy sector, the National Operator of Electric System (ONS). Climate research activities were conducted through interactions between climate researchers, energy sector personnel and social scientists, focusing on applications. WP1- Physical processes explaining climate variability in South America, aimed to study the remote and regional features associated with precipitation extremes over South America, with emphasis on regions where the main hydrographic basins are located. WP2- Predictability and Prediction tools developed several studies, mainly at the sub-seasonal timescale, which was a timescale identified to be useful for ONS. WP3- Social processes explaining climate information appropriation were composed of social scientists and had the mission of producing a characterization of the electric sector. Here, some of the WP1 and WP2 results are summarized, illustrating the potential applications. WP0 and WP3 results are presented in other papers.